Reforming Education Features in the XXI-st Century Сhallenges - Vasyliuk, Alla (Pedagogical Discourse, 2015)
The article outlines the society features of the XXI-st century. The analysis of these features, real and anticipated trends in education reform in a global context has been fulfilled. Transition from knowledge to competence educational paradigm has been accented. Highlighted competencies are: key; general and intended. It is revealed that the common areas of change include: the introduction of new educational standards and strategies for assessing the institutions’ quality of education, upgrading curriculums (in compliance with optimal proportion between the transfer of knowledge and methodology of receipt), and priority in transmission operational rather than encyclopedic knowledge to pupils and students. The need for such learning theory able to orient education toward a new way of thinking and new stimuli for life of future generations is accented. There is a new division of responsibility for the functioning of education. It is indicated on the main goals of global education and innovative features of current reforms. Noticeable trend of institutional reform with the transition to higher autonomy of schools is underlined. A problem concerning the privatization of education is also outlined.